ELECTRICAL CONDUCTIVITY AS A TOOL FOR EVALUATION OF SPECIAL BEANS - souza de lima, Elaine; dos Santos Oliveira, Andréa; Tatiana de Almeida, Tanismare; Silva Filho, Pedro; Laranjeira dos santos , Mariana (Journal of Interdisciplinary Debates, 2025)
Special beans, belonging to the genera Vigna and Phaseolus, are legumes of great nutritional and economic importance, widely cultivated for human and animal consumption. The most common species include cowpea (Vigna unguiculata), mung bean (Vigna radiata), azuki bean (Vigna angularis), and black bean (Phaseolus vulgaris). The quality of the seeds of these legumes is essential to ensure the success of agricultural production, as high-quality seeds result in greater vigor and productivity. Thus, the objective of this study was to evaluate the quality of special bean seeds used by producers in the state of Mato Grosso. The experiment was conducted at the Seed Studies and Analysis Center (CEAS) of the University of the State of Mato Grosso, using 12 bean cultivars, with 4 replications. The tests performed included purity, moisture, thousand-seed weight, germination, emergence, tetrazolium, and electrical conductivity. The purity analysis followed the guidelines of Brazil (2009), and the germination assessment was conducted according to the specific conditions for each species. For the electrical conductivity test, the seeds were soaked in water for different periods, and the readings were taken for various combinations of seed quantities and soaking times. The experimental design was completely randomized, with data analysis performed using the Scott- Knott test and Pearson correlation analysis. Species grouping was carried out using the Tocher method and hierarchical UPGMA analysis. The research aims to provide information on the quality of seeds used by producers, enabling better practices to optimize production and ensure the quality of bean crops in the state.